TO THE ISSUE OF JURISDICTION OF INDIVIDUAL LABOUR DISPUTES IN THE REPUBLIC OF KAZAKHSTAN - Galiakbarova Гузаль Газинуровна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
Nowadays the legal regulation of individual labor disputes is one of the most topical issues in the Republic of Kazakhstan. Determining jurisdiction of individual labor disputes is characterized by its relevance.